Organizational Communication Between Principals, Educators, and Educational Staff of ElementaryEducation Institution - Mesiono Mesiono; Abdul Latif Hutagaol; Siti Rahma Ismiatun; Muhammad Rizki Dermawan Saragih; Elfin Nazri (Universitas Pahlawan Tuanku Tambusai, 2023)
Communication of school principals with subordinates is one of the determining factors for the success or failure of school governance. This study aims to analyze the communication patterns of the principal with teachers and education staff at SDN 16 Bilah Barat. This type of research includes qualitative with descriptive analytical study method. Collecting research data using the method of observation, interviews and documentation studies. Next, the data were analyzed using data reduction techniques, data presentation, and conclusions. Test the validity of the research using data triangulation techniques. The results of this study concluded that the communication built by the school principal was considered effective. This can be seen from the application of 2 communication patterns, namely First the school principal uses a chain pattern in announcements received from the head of the school's superiors who will share the information with teachers and education staff. The principal also uses a chain pattern in giving warnings to his members. Second, the communication patterns of all channels are also used by school principals, educators and education staff in their daily lives at school. Everyone can communicate with each other without going through any intermediaries. Thus, effective communication patterns are carried out in elementary schools.